FAIR in action: Brain-CODE - A neuroscience data sharing platform to accelerate brain research - Behan, Brendan; Jeanson, Francis; Cheema, Heena; Eng, Derek; Khimji, Fatema; Vaccarino, Anthony L.; Gee, Tom; Evans, Susan G.; MacPhee, F. Chris; Dong, Fan; Shahnazari, Shahab; Sparks, Alana; et al. (Frontiers in Neuroinformatics, 2023)
The effective sharing of health research data within the healthcare ecosystem can have tremendous impact on the advancement of disease understanding, prevention, treatment, and monitoring. By combining and reusing health research data, increasingly rich insights can be made about patients and populations that feed back into the health system resulting in more effective best practices and better patient outcomes. To achieve the promise of a learning health system, data needs to meet the FAIR principles of findability, accessibility, interoperability, and reusability (Wilkinson et al., 2016). Since the inception of the Brain-CODE platform and services in 2012, the Ontario Brain Institute (OBI) has pioneered data sharing activities aligned with FAIR principles in neuroscience (Vaccarino et al., 2018). Here, we describe how Brain-CODE has operationalized data sharing according to the FAIR principles: Findable – Brain-CODE offers an interactive and itemized approach for requesters to generate data cuts of interest that align with their research questions. Accessible – Brain-CODE offers multiple data access mechanisms. These mechanisms – that distinguish between metadata access, data access within a secure computing environment on Brain-CODE and data access via export will be discussed. Interoperable – Standardization happens at the data capture level and the data release stage to allow integration with similar data elements. Reusable - Brain-CODE implements several quality assurances measures and controls to maximize data value for reusability. We will highlight the successes and challenges of a FAIR-focused neuroinformatics platform that facilitates the widespread collection and sharing of neuroscience research data for learning health systems.